Strategy Analysis of Ponggok Rural Tourism Development into Integrated Tourism Area - Satriawati, Zahrotun; Ingkadijaya, Rahmat; Sulartiningrum, Sri (Institut Pariwisata Trisakti, 2019)
The development of tourism can help the welfare of the rural population through developing a tourist village concept. The potential of the village can be used as a tourist attraction. Klaten Regency has a very abundant potential of springs that located in Ponggok village which is mostly used by local residents for irrigating rice fields, agriculture, and fish cultivation. However, the existing springs in the Ponggok village are now used as tourist destinations that spread across several locations, such as Umbul Ponggok, Umbul Sigedang, Umbul Besuki, Waduk Galau/Banyu Mili. This study uses qualitative and quantitative descriptive analysis and the data obtained through questionnaires distributed and completed by respondents as many as 135 respondents. SWOT analysis is employed to investigate internal and external factors to analyze Ponggok Tourism Village development strategy towards integrated tourism area.